Audio–visual interaction in visual motion detection: Synchrony versus Asynchrony - Rosemann, Stephanie (J Optom, 2017)
OBJECTIVE: Detection and identification of moving targets is of paramount importance in everyday life, even if it is not widely tested in optometric practice, mostly for technical reasons. There are clear indications in the literature that in perception of moving targets, vision and hearing interact, for example in noisy surrounds and in understanding speech. The main aim of visual perception, the ability that optometry aims to optimize, is the identification of objects, from everyday objects to letters, but also the spatial orientation of subjects in natural surrounds. To subserve this aim, corresponding visual and acoustic features from the rich spectrum of signals supplied by natural environments have to be combined. METHODS: Here, we investigated the influence of an auditory motion stimulus on visual motion detection, both with a concrete (left/right movement) and an abstract auditory motion (increase/decrease of pitch). RESULTS: We found that incongruent audiovisual stimuli led to significantly inferior detection compared to the visual only condition. Additionally, detection was significantly better in abstract congruent than incongruent trials. For the concrete stimuli the detection threshold was significantly better in asynchronous audiovisual conditions than in the unimodal visual condition. CONCLUSION: We find a clear but complex pattern of partly synergistic and partly inhibitory audio–visual interactions. It seems that asynchrony plays only a positive role in audiovisual motion while incongruence mostly disturbs in simultaneous abstract configurations but not in concrete configurations. As in speech perception in hearing-impaired patients, patients suffering from visual deficits should be able to benefit from acoustic information.